Efficacy and Tolerability of Hybrid Complexes of High- and Low-Molecular-Weight Hyaluronan Intradermal Injections for the Treatment of Skin Roughness and Laxity of the Neck - Adele Sparavigna; Laura Bombelli; Andrea Maria Giori; Gilberto Bellia (The Scientific World Journal)
This study aimed to evaluate the efficacy of a well-characterized formulation of hyaluronic acid (HA), Profhilo®, in the treatment of roughness and laxity of the neck skin. The study was performed on 25 subjects ranging in age from 40 to 65 years. Two injections of the studied product at 30-day intervals were performed, with evaluations conducted 1 and 4 months after the first injection. The efficacy was determined by clinical and multilevel instrumental evaluations. In addition, at the end of the study, the subjects completed a questionnaire related to the efficacy and tolerability of the product. The studied product was shown to induce a clear and statistically significant improvement in the skin of the neck in all the subjects, with concordant results between the clinical, instrumental, and subjects’ evaluations. The positive effects, present after the first injection, were further increased in the second and last evaluation. Notably, the product was reported to have a very high tolerability by both clinicians and subjects. In conclusion, two injections of the studied product safely induced skin amelioration in subjects with mild to moderate neck skin roughness and laxity.